TINDAK TUTUR DIREKTIF GURU BAHASA INDONESIA DAN RESPON SISWA DALAM PROSES BELAJAR MENGAJAR DI KELAS IX SMP NEGERI 26 PADANG - Ermazati Arief, Melisa Eki Saputri, Emidar, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this research are describing the form, strategy, and context of using speech act strategy which are positively and negatively responded by the students in teaching and learning process in class IX at SMPN 26 Padang. The type of this research is a qualitative research descriptive. (3) Method within the data such as the teachers’ speech act and students’ respond in teaching and learning process. The technique used in collecting the data is recording technique. Based on the research discovery and discussion, the writer concludes the terms below. There are five types of directive speech act asking, desiring, suggesting, demanding, and challenging. These types of directive speech act are expressed by using four types of speaking; they are speaking frankly without politeness, speaking frankly with positive politeness, speaking frankly with negative politeness, and speaking obscurely in teaching and learning process in different situations. That teacher’s speech acts are responded differently by the students. The responds can be a respond of positive verbal, negative verbal, positive nonverbal and negative nonverbal. Kata kunci:  direktif, strategi, konteks, respon siswa